Zealandozetes southensis gen. nov., sp. nov. (Acari, Oribatida, Maudheimiidae) from alpine cushions plant in New Zealand - Ermilov, Sergey G.; Minor, Maria A.; Behan-Pelletier, Valerie M. (Zootaxa, 2015)
A new oribatid mite genus, Zealandozetes gen. nov. (Oribatida, Maudheimiidae), with type species Zealandozetes southensis sp. nov., is proposed and described based on adult and juvenile instars. It inhabits the soil under and around cushion-forming plants in the high-altitude alpine zone of two mountain ranges (the Pisa Range and The Remarkables) in the South Island of New Zealand. It is distinguished from species of Maudheimia by having pteromorphs reduced to pleural carinae, notogastral saccules, small pedotecta I, and both postanal porose area and Ah expressed as complex saccules. Juveniles are similar to those of Maudheimia, except the humeral organ of Z. southensis is cupule-like and gastronotic microsclerites are lacking. We give a revised diagnosis for Maudheimiidae and discuss both supportive and contradictory evidence for inclusion of Zealandozetes. Finally, we discuss endemism of Zealandozetes with reference to the knowledge of New Zealand biogeography and its oribatid fauna.